Retrospective and new records of hard ticks (Acari: Ixodidae) on wild animals from Paraná State, southern of Brazil - Valente, Jessica D. M.; Kakimori, Monica T. A.; Silva, Patrícia W.; Arzua, Márcia; Barros-Battesti, Darci M. [UNESP]; Saldanha, André; Martini, Rafaella; Lange, Rogério R.; Martins, Thiago F.; Vieira, Thállitha S. W. J.; Labruna, Marcelo B.; Vieira, Rafael F. C. (Systematic and Applied Acarology Society, 2022)
Ticks are distributed worldwide, and in South America, Brazil possesses the largest diversity of them. They are responsible for transmitting a wide range of pathogens to animals and accidentally to humans. The available data on tick species parasitizing wild animals in Paraná State are limited to few reports. Accordingly, the aims of this study were to describe and map the distribution of ticks parasitizing wild animals in Paraná State, southern Brazil, based on unpublished data from records of ticks deposited in two scientific collections, and tick records from previously published studies. Overall, we obtained 976 records of parasitism by ticks from 173 different species of free-ranging wild animals: 2/173 (1.2%) amphibians, 2/173 (1.2%) reptiles, 119/173 (68.8%) birds, 3/173 (1.7%) canids, 2/173 (1.2%) deer, 6/173 (3.5%) felids, 7/173 (4.0%) marsupials, 3/173 (1.7%) mustelid, 2/173 (1.2%) non-human primates, 2/173 (1.2%) procionid, 19/173 (11.0%) rodents, 2/173 (1.2%) Suine, 1/173 (0.6%) tapir, and 3/173 (1.7%) Xenarthra. A total of 6,794 ticks (1,163 males, 749 females, 428 adults of non-defined sex, 1,824 nymphs, 2,370 larvae, and 260 not identified stages) were recorded. The following tick species were recorded: Amblyomma aureolatum, Amblyomma brasiliense, Amblyomma calcaratum, Amblyomma coelebs, Amblyomma dissimile, Amblyomma dubitatum, Amblyomma fuscum, Amblyomma geayi, Amblyomma incisum, Amblyomma longirostre, Amblyomma nodosum, Amblyomma ovale, Amblyomma parkeri (some published as A. geayi), Amblyomma parvum, Amblyomma pseudoconcolor, Amblyomma rotundatum, Amblyomma sculptum (some published as Amblyomma cajennense senso lato), Amblyomma tigrinum, Amblyomma triste, Amblyomma sp., Haemaphysalis juxtakochi, Haemaphysalis sp., Ixodes auritulus, Ixodes fuscipes (some published as Ixodes aragaoi), Ixodes loricatus, Ixodes paranaensis, Ixodes schulzei, Ixodes sp., and Rhipicephalus microplus. Amblyomma aureolatum and A. longirostre were highly prevalent on wild hosts. Ring-tailed coati (Nasua nasua) was the host species with the highest tick richness in Paraná State, Brazil. Also, we provide the first record of the tick-host association A. fuscum on felid (Leopardus guttulus), and R. microplus on rodent (Sphiggurus villosus).
Keywords: Amblyomma; Haemaphysalis; Ixodes; Rhipicephalus; wild hosts